External shear strengthening of RC beams with basalt fiber sheets: An experimental study. (June 2021) - Kar, Swapnasarit; Biswal, K.C.
Abstract: Basalt fiber is an eco-friendly fiber and a promising material for the strengthening of reinforced concrete (RC) structures due to its various advantages such as low cost, better resistance to chemical attack, good thermal characteristics and higher tensile strength than the E-glass fiber. However, only a few experimental investigations have been reported in the literature on the strengthening of RC beams with basalt fiber reinforced polymer (BFRP) composites. Therefore, the current study targets to investigate the efficacy of basalt fiber sheets as a shear strengthening material for RC beams. Ten RC beams were examined under the four-point loading system. The influence of different parameters such as width, orientation and amount of the BFRP strips, type of strengthening schemes, type of fiber sheets (glass and basalt) and the effect of the level of pre-loading were investigated in the present study. The experimental outcomes have shown that the failure load of strengthened beams increased by 17–50%, whereas the toughness enhanced up to 2.74 times in comparison to the reference specimen. In addition, it has been noticed from the current investigation that the overall effectiveness of basalt fiber sheets in increasing the shear capacity is 20% higher than that of the glass fiber sheets and the enhancement in shear capacity decreases with an increase in preload level.